2020
DOI: 10.1108/srj-12-2019-0401
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility, innovation capability and firm performance: evidence from SME

Abstract: Purpose The purpose of this paper is to examine corporate social responsibility (CSR) and its effect on small and medium enterprises’ (SMEs) innovation capability and financial performance from the perspective of a developing country. It also aims to explore the role of innovation capability as a mediating factor in the linkage between CSR and SMEs’ financial performance. Design/methodology/approach A questionnaire was distributed among managers/owners of the sampled companies. Using a data set of 402 Eritre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
1
33

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 124 publications
8
53
1
33
Order By: Relevance
“…This approach has become a popular approach (method) and is most frequently used for testing complex models (path models) with latent constructs and associations among them (Sarstedt et al, 2017). It is an essential statistical method (technique) that researchers from different disciplines, especially social sciences and marketing, regularly use to analyze the data (Bahta et al, 2021;Begum et al, 2021;Hair et al, 2019;Waheed et al, 2021). PLS-SEM is compatible with a small sample size, and it allows researchers to use the HTMT criterion for testing the discriminant validity (Hair et al, 2019).…”
Section: Analysis Tools and Resultsmentioning
confidence: 99%
“…This approach has become a popular approach (method) and is most frequently used for testing complex models (path models) with latent constructs and associations among them (Sarstedt et al, 2017). It is an essential statistical method (technique) that researchers from different disciplines, especially social sciences and marketing, regularly use to analyze the data (Bahta et al, 2021;Begum et al, 2021;Hair et al, 2019;Waheed et al, 2021). PLS-SEM is compatible with a small sample size, and it allows researchers to use the HTMT criterion for testing the discriminant validity (Hair et al, 2019).…”
Section: Analysis Tools and Resultsmentioning
confidence: 99%
“…Dapat disimpulkan bahwa, relational quality memiliki pengaruh positif dan signifikan terhadap kapabilitas inovasi H7 : Relational quality berpengaruh positif dan signifikan terhadap kapabilitas inovasi. Bahta et al, (2021), tentang kapabilitas inovasi mampu meningkatkan kinerja bisnis. Saunila (2014) tentang kapabilitas inovasi mampu meningkatkan kinerja keuangan; Liao et al, (2020), menemukan bahwa kapabilitas inovasi berpengaruh positif dan signifikan terhadap kinerja bisnis termasuk kinerja keuangan.…”
Section: H2unclassified
“…Hasil penelitian ini sekaligus memperkuat hasil penelitian sebelumnya yang dilakukan oleh Bahta et al, (2021), tentang kapabilitas inovasi mampu meningkatkan kinerja bisnis. Saunila (2014) tentang kapabilitas inovasi mampu meningkatkan kinerja keuangan; Liao et al, (2020), menemukan bahwa kapabilitas inovasi berpengaruh positif dan signifikan terhadap kinerja bisnis termasuk kinerja keuangan.…”
Section: Tabel 6 Indirect Effectsunclassified
“…It could be observed that several studies have provided significant outcomes in enhancing SMEs' performance in developing countries (Alosani et al, 2020;Bahta et al, 2020;Eniola et al, 2019;Kiyabo & Isaga, 2019). However, few studies provide effective antecedents, variables, and models that impact SMEs' performance, leading to their weak performance in developing countries (G. , particularly in Kuwait (Abu-Aisheh, 2018;Al-duwailah et al, 2019;Alzougool, 2019).…”
Section: Organizational Performancementioning
confidence: 99%